Inhibition of P-glycoprotein - Mediated Efflux of Digoxinand Its Metabolites by Macrolide Antibiotics - Hughes, Jeffery; Crowe, Andrew (The Japanese Pharmacological Society, 2010)
This study was conducted to determine the rate of P-glycoprotein (P-gp) mediated efflux of digoxin analogues and metabolites, and to assess the effects of macrolide antibiotics on this efflux. Bidirectional transport studies were conducted using our Caco-2 sub clone with high P-gp expression (CLEFF9). HPLC methods were employed to measure drug transport. All digoxin metabolites were P-gp substrates, although digoxin had the greatest efflux ratio. Erythromycin had no effect on the transport of digoxin, maintaining a Basolateral to apical efflux ratio of 14.8, although it did reduce the efflux ratio of dihydrodigoxin and digoxigenin by 34% and 43%, respectively. Azithromycin also had little effect on the transport of digoxin or any of its metabolites. In contrast, clarithromycin and roxithromycin almost eliminated basolateral targeted efflux. Using paclitaxel as a known P-gp substrate, erythromycin demonstrated only partial P-gp inhibitory capacity maintaining an efflux ratio over 100. In contrast, clarithromycin and roxithromycin were 10 fold greater P-gp inhibitors. Clarithromycin and roxithromycin are likely to exhibit drug interactions with digoxin via inhibition of efflux mechanisms. Azithromycin appears to have little influence on P-gp mediated digoxin absorption or excretion and would be the safest macrolide to use concurrently with oral digoxin.